To find the x-intercept(s), substitute in <math><mstyle displaystyle="true"><mn>0</mn></mstyle></math> for <math><mstyle displaystyle="true"><mi>y</mi></mstyle></math> and solve for <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> .

Solve the equation.

Rewrite the equation as <math><mstyle displaystyle="true"><msup><mrow><mi>x</mi></mrow><mrow><mn>2</mn></mrow></msup><mo>-</mo><mn>6</mn><mi>x</mi><mo>+</mo><mn>8</mn><mo>=</mo><mn>0</mn></mstyle></math> .

Factor <math><mstyle displaystyle="true"><msup><mrow><mi>x</mi></mrow><mrow><mn>2</mn></mrow></msup><mo>-</mo><mn>6</mn><mi>x</mi><mo>+</mo><mn>8</mn></mstyle></math> using the AC method.

Consider the form <math><mstyle displaystyle="true"><msup><mrow><mi>x</mi></mrow><mrow><mn>2</mn></mrow></msup><mo>+</mo><mi>b</mi><mi>x</mi><mo>+</mo><mi>c</mi></mstyle></math> . Find a pair of integers whose product is <math><mstyle displaystyle="true"><mi>c</mi></mstyle></math> and whose sum is <math><mstyle displaystyle="true"><mi>b</mi></mstyle></math> . In this case, whose product is <math><mstyle displaystyle="true"><mn>8</mn></mstyle></math> and whose sum is <math><mstyle displaystyle="true"><mo>-</mo><mn>6</mn></mstyle></math> .

Write the factored form using these integers.

Set <math><mstyle displaystyle="true"><mi>x</mi><mo>-</mo><mn>4</mn></mstyle></math> equal to <math><mstyle displaystyle="true"><mn>0</mn></mstyle></math> and solve for <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> .

Set the factor equal to <math><mstyle displaystyle="true"><mn>0</mn></mstyle></math> .

Add <math><mstyle displaystyle="true"><mn>4</mn></mstyle></math> to both sides of the equation.

Set <math><mstyle displaystyle="true"><mi>x</mi><mo>-</mo><mn>2</mn></mstyle></math> equal to <math><mstyle displaystyle="true"><mn>0</mn></mstyle></math> and solve for <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> .

Set the factor equal to <math><mstyle displaystyle="true"><mn>0</mn></mstyle></math> .

Add <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> to both sides of the equation.

The solution is the result of <math><mstyle displaystyle="true"><mi>x</mi><mo>-</mo><mn>4</mn><mo>=</mo><mn>0</mn></mstyle></math> and <math><mstyle displaystyle="true"><mi>x</mi><mo>-</mo><mn>2</mn><mo>=</mo><mn>0</mn></mstyle></math> .

x-intercept(s) in point form.

x-intercept(s): <math><mstyle displaystyle="true"><mrow><mo>(</mo><mn>4</mn><mo>,</mo><mn>0</mn><mo>)</mo></mrow><mo>,</mo><mrow><mo>(</mo><mn>2</mn><mo>,</mo><mn>0</mn><mo>)</mo></mrow></mstyle></math>

x-intercept(s): <math><mstyle displaystyle="true"><mrow><mo>(</mo><mn>4</mn><mo>,</mo><mn>0</mn><mo>)</mo></mrow><mo>,</mo><mrow><mo>(</mo><mn>2</mn><mo>,</mo><mn>0</mn><mo>)</mo></mrow></mstyle></math>

To find the y-intercept(s), substitute in <math><mstyle displaystyle="true"><mn>0</mn></mstyle></math> for <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> and solve for <math><mstyle displaystyle="true"><mi>y</mi></mstyle></math> .

Solve the equation.

Remove parentheses.

Simplify <math><mstyle displaystyle="true"><msup><mrow><mo>(</mo><mn>0</mn><mo>)</mo></mrow><mrow><mn>2</mn></mrow></msup><mo>-</mo><mn>6</mn><mo>⋅</mo><mn>0</mn><mo>+</mo><mn>8</mn></mstyle></math> .

Simplify each term.

Raising <math><mstyle displaystyle="true"><mn>0</mn></mstyle></math> to any positive power yields <math><mstyle displaystyle="true"><mn>0</mn></mstyle></math> .

Multiply <math><mstyle displaystyle="true"><mo>-</mo><mn>6</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>0</mn></mstyle></math> .

Simplify by adding zeros.

Add <math><mstyle displaystyle="true"><mn>0</mn></mstyle></math> and <math><mstyle displaystyle="true"><mn>0</mn></mstyle></math> .

Add <math><mstyle displaystyle="true"><mn>0</mn></mstyle></math> and <math><mstyle displaystyle="true"><mn>8</mn></mstyle></math> .

y-intercept(s) in point form.

y-intercept(s): <math><mstyle displaystyle="true"><mrow><mo>(</mo><mn>0</mn><mo>,</mo><mn>8</mn><mo>)</mo></mrow></mstyle></math>

y-intercept(s): <math><mstyle displaystyle="true"><mrow><mo>(</mo><mn>0</mn><mo>,</mo><mn>8</mn><mo>)</mo></mrow></mstyle></math>

List the intersections.

x-intercept(s): <math><mstyle displaystyle="true"><mrow><mo>(</mo><mn>4</mn><mo>,</mo><mn>0</mn><mo>)</mo></mrow><mo>,</mo><mrow><mo>(</mo><mn>2</mn><mo>,</mo><mn>0</mn><mo>)</mo></mrow></mstyle></math>

y-intercept(s): <math><mstyle displaystyle="true"><mrow><mo>(</mo><mn>0</mn><mo>,</mo><mn>8</mn><mo>)</mo></mrow></mstyle></math>

Do you know how to Find the X and Y Intercepts y=x^2-6x+8? If not, you can write to our math experts in our application. The best solution for your task you can find above on this page.

Name | one billion six hundred nineteen million one hundred twelve thousand one hundred thirty |
---|

- 1619112130 has 16 divisors, whose sum is
**3085837560** - The reverse of 1619112130 is
**0312119161** - Previous prime number is
**17**

- Is Prime? no
- Number parity even
- Number length 10
- Sum of Digits 25
- Digital Root 7

Name | three hundred ninety-three million eight hundred seventy thousand nine hundred seventy-three |
---|

- 393870973 has 4 divisors, whose sum is
**393914080** - The reverse of 393870973 is
**379078393** - Previous prime number is
**13147**

- Is Prime? no
- Number parity odd
- Number length 9
- Sum of Digits 49
- Digital Root 4

Name | eight hundred twenty-one million one hundred forty-six thousand five hundred eighty-four |
---|

- 821146584 has 64 divisors, whose sum is
**3698571456** - The reverse of 821146584 is
**485641128** - Previous prime number is
**1123**

- Is Prime? no
- Number parity even
- Number length 9
- Sum of Digits 39
- Digital Root 3